A Cross-sectional Study on Caffeine Dependency by Drinking Tea and Coffee Among Bangladeshi Students - Munia, Ashfia Tasnim; Bondhon, Saif Bin Salam; Sarkar, Md Raihan; Rahman, Rabita; Sikdar, KM Yasif Kayes; Samadd, Md Abdus (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Too much caffeine consumption might cause physical and mental dependency on the consumer. This study examined the socio-demographic factors, knowledge, behavior, and perception of Bangladeshi students about caffeine which is based on drinking tea and coffee. This questionnaire-based study included 1020 respondents from primary level to postgraduate level students. The analysis utilized frequencies, means, percentages, Pearson's chi-square (χ2) statistic and Spearman's rank correlation coefficients. Pearson's chi-square (χ2) statistic test was performed to determine the significance at 5% with a p-value < 0.05. Most of the students (94.8%) consume tea or coffee regularly, and 66.1% drink it daily. A total of 87.5% of students knew that tea and coffee have caffeine. Nearly two-thirds (67.1%) of the students were dependent on tea and coffee, and 35.9% experienced psycho-physiological alterations after a day without drinking those items. About 38% of students noticed side effects after consumption of tea or coffee multiple times in a day. This study also reveals that gender did not alter the knowledge or drinking behavior of tea and coffee. Tea and coffee drinking patterns were not significantly dependent upon the participants’ educational qualifications. Dhaka Univ. J. Pharm. Sci. 22(2): 202-212, 2023 (December)